MEASURING DEVICE OF FLASHES RM 301 - E. I. Kukuruisnjak; T. V. Kozlova; M. P. Kovalenko (Литьë и металлургия)
The methods of measuring of relative area of hardware tie with the help of traditional measuring methods and measuring using device RM301.